Method and Device for Production of Driving Force in Underwater Floating Vehicle - Auzins, Janis; Eimanis, Marcis (Recent Patents on Mechanical Engineering, 2021)
Background: In this paper, we present a completely new type of propulsion system where thrust force is created by the helicoidal shape of the hull rather than screw propellers. The method and device have been recently patented. The inspiration comes from nature, the world of bacteria, where some organisms have been using the drilling motion or rotating flagella to move in fluid media for several million years. The hull of device consists of three parts – bow and stern (which create the propulsion force) and the middle part which can serve as a cargo compartment containing all control mechanisms and communications. The Cardan-joint mechanism that allows changing the direction of the vehicle is actuated by bending drives. A bending drive velocity control algorithm is proposed for the automatic control of vehicle movement direction. Objective: Development of a new propulsion system for underwater vehicles. Methods: The watercraft dynamics were simulated using multibody simulation software MSC Adams. For accurate interaction with medium, polynomial metamodels were created on the basis of computer experiments with CFD software. Computational Fluid Dynamics software was used for flow interaction with the prototype geometry, implementing the same idea that is used in wind tunnel experiments. Results and Conclusion: The results are compared with measurements of the physical prototype, built at the Institute of Mechanics and Mechanical Engineering of Riga Technical University. These results showed good validation with mathematical simulation and confirmed the effectiveness and future potential of the proposed principle.
Keywords: Autonomous underwater vehicle